PSICOPATHOLOGY OF UNEMPLOYMENT - Buendía, José (Anales de Psicología / Annals of Psychology)
The psychological impact caused by unemployment, considered to be one of life’s most stressful events, is examined. The psychological effects which unemployment most frequently produces are highlighted, particularly an increase in depressive symptomatology, feelings of insecurity and of failure, loss of self-esteem and the deterioration of family and social relationships. Attention is especially focused on the analysis of factors which moderate its impact, among which conscious social support stands out, helping with the cognitive aspects of problem solving and reaffirming the personal identity of the individual, thus increasing the range of coping strategies at his disposal.